The tropical African hermit crab Pagurus mbizi (Crustacea, Decapoda, Paguridae) in the Western Mediterranean Sea: a new alien species or filling gaps in the knowledge of the distribution? - GARCIA RASO, J. E.; SALMERON, F.; BARO, J.; MARINA, P.; ABELLO, P. (Mediterranean Marine Science, 2013)
We report the first occurrence in the European Mediterranean Sea of a tropical Atlantic hermit crab, Pagurus mbizi (Forest, 1955), based on the capture of twenty specimens (all sizes and ovigerous females) collected along the northern shores of the Alboran Sea, which proof the existence of a well-established population of this species, and the importance of this geographic area as a transitional and settlement zone for Atlantic species, which makes the Alboran Sea one of the richest marine biodiversity areas in the Mediterranean Sea. Some morphological comparative data with the closely related hermit crab Pagurus pubescentulus are given. In addition, data on its habitat and geographical distribution, as well as the probable pathways of introduction, are commented.